Seawater in-situ hydrogen production method

By using the IPN film prepared by crosslinked polyvinyl alcohol and hydrophobic polyamic acid precursor as the phase transition mass transfer layer, the problem that materials in the prior art are difficult to have both hydrophobicity and water vapor permeability, and high-efficiency and low-cost in-situ hydrogen production in seawater is achieved.

CN119553314AActive Publication Date: 2025-03-04WUHAN UNIV OF TECH +1

Patent Information

Application Number
CN202411668282.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-04
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

In the existing in-situ hydrogen production technology of seawater, the phase change mass transfer layer material is difficult to have high hydrophobicity and good water vapor permeability, resulting in equipment corrosion and inefficiency.

Method used

The phase-change mass transfer layer is prepared by IPN film technology using crosslinked polyvinyl alcohol and hydrophobic polyamic acid precursor. Modification by crosslinking agent and fluorinating agent is used to balance the hydrophilicity and hydrophobicity, and the corrosion resistance and mechanical strength of the film are improved.

Benefits of technology

The phase-transformation mass transfer layer has high hydrophobicity and good water vapor permeability, which improves the efficiency of in-situ electrolysis of seawater, reduces costs, and improves the stability and yield of the membrane material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553314A_ABST
    Figure CN119553314A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrolytic hydrogen production, and particularly relates to a seawater in-situ hydrogen production method. According to the method, a phase change mass transfer tank is included and comprises a seawater area (1), a phase change mass transfer layer (2) and an electrolyte area (3); seawater is discharged from a seawater tank, sequentially passes through a prefilter, a first-stage heat exchanger and a second-stage heat exchanger, and enters the seawater area (1) for phase change mass transfer; electrolyte enters the electrolyte area (3) from the electrolyte mixing tank; the phase-change mass transfer is carried out at the phase-change mass transfer layer (2), and the phase-change mass transfer layer (2) is an IPN film; and discharging from the electrolyte area (3) to an electrolytic cell for electrolytic hydrogen production. The IPN membrane is prepared from polyvinyl alcohol and polyimide, and through a series of modification measures such as fluorination, it is ensured that the IPN membrane has high hydrophobicity and good water vapor permeability, so that the efficiency of electrolytic hydrogen production is improved; in addition, the IPN film is simple and convenient to prepare and operate and high in yield.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrolytic hydrogen production, and specifically relates to a method for in-situ hydrogen production from seawater. Background Art

[0002] Green hydrogen refers to hydrogen produced by using renewable energy such as solar energy and wind energy to generate electricity and then electrolyzing water to produce hydrogen. Compared with gray hydrogen or blue hydrogen, green hydrogen achieves zero carbon emissions from the entire process from production to use, and is a truly clean energy. However, the vast majority of the earth's water resources are seawater, and other available freshwater resources such as rivers, lakes or groundwater are difficult to meet the human society's demand for future hydrogen energy. In order to further promote the production and application of green hydrogen, seawater electrolysis hydrogen production technology has attracted more and more attention from today's scientific and industrial communities. However, since seawater contains a large amount of impurities such as chloride ions and microorganisms, these impurities will produce side reactions such as chlorine evolution reactions at the electrodes during electrolysis, which will accelerate the corrosion of electrode materials and equipment. To solve this problem, the current seawater electrolysis hydrogen production technology routes mainly include electrolysis hydrogen production after seawater desalination and in-situ seawater electrolysis hydrogen production. Among them, in-situ seawater electrolysis hydrogen production eliminates the desalination step compared to seawater electrolysis hydrogen production, and has the advantages of lower energy consumption and higher production efficiency. The technical principle is to install a hydrophobic breathable membrane in the phase change mass transfer device, with seawater and potassium hydroxide electrolyte on both sides of the hydrophobic breathable membrane. The water saturated vapor pressure difference caused by the different ion concentrations on the seawater side and the electrolyte side is used to achieve evaporation and mass transfer of water vapor from the seawater side to the electrolyte side, thereby transferring water molecules from seawater to the potassium hydroxide electrolyte, and finally electrolyzing water in the electrolysis device to produce hydrogen. The key points of this technology are that the hydrophobic breathable membrane must be sufficiently hydrophobic to block seawater and prevent impurity ions such as Cl⁻ from penetrating into the electrolyte to cause pollution, and that the migration efficiency of gas-phase water molecules must be guaranteed; in addition, it is also required to have certain corrosion resistance and mechanical strength.

[0003] Chinese patent CN114481164A discloses a non-pure aqueous solution electrolysis hydrogen production device, system and method based on liquid phase moisture absorption, the device includes an electrolyte layer, a water vapor mass transfer layer and an oxygen evolution catalytic layer attached to both sides of the electrolyte layer, the device also includes a hydrogen evolution catalytic layer and an ion exchange membrane located between the oxygen evolution catalytic layer and the hydrogen evolution catalytic layer, the oxygen evolution catalytic layer is provided with an anode electrode, and the hydrogen evolution catalytic layer is provided with a cathode electrode. Among them, the water vapor mass transfer layer is one of a TPU membrane, PDMS, and PTFE membrane with a pore size of 0.1 to 100µm, or a porous water vapor mass transfer layer prepared by spraying, screen printing, and electrostatic adsorption of graphene, PVDF particles, and PTFE particles. In this patent, the hydrogen evolution catalytic layer, the ion exchange membrane, and the oxygen evolution catalytic layer play a similar function to that of an electrolytic cell, while the water vapor mass transfer layer plays a phase change mass transfer function.

[0004] Chinese patent CN113088986A discloses a device, system and method for in-situ self-capture of hydrogen production from seawater based on polyelectrolyte gel, wherein the waterproof and breathable layer used is a PTFE waterproof and breathable membrane, TPU waterproof and breathable membrane or PDMS waterproof and breathable membrane with a pore size of 0.1 to 100µm, or a porous waterproof and breathable layer prepared by spraying, screen printing or electrostatic adsorption of hydrophobic materials. In this patent, the waterproof and breathable layer plays the role of phase change mass transfer.

[0005] The above patent has the following disadvantages: the membrane material used in the phase change mass transfer layer should have high hydrophobicity, making it difficult for seawater to spread on the membrane surface, preventing impurities such as chloride ions from penetrating into the electrolyte, thereby corroding the equipment and reducing the life of the electrode; it also needs to have a certain degree of hydrophilicity, that is, water vapor microdroplets can form good contact with the membrane surface through hydrogen bonds and other effects to ensure good water vapor permeability, so as to improve the efficiency of hydrogen production by electrolysis. Therefore, the microstructure of the selected membrane material should have a suitable porosity, pore size and hydrophilicity / hydrophobicity balance. However, single-material materials such as TPU membranes, PDMS or PTFE membranes are difficult to balance hydrophilicity and hydrophobicity before modification; in addition, the preparation of porous water vapor mass transfer layers by spraying, screen printing or electrostatic adsorption has high requirements on equipment accuracy and operators, and the corresponding cost will also be higher.

[0006] Therefore, based on the technical requirements of phase change mass transfer, whether a low-cost and high-yield method can be found to prepare membrane materials that have both high hydrophobicity and good water vapor permeability is the key point in determining whether seawater in situ hydrogen production technology can be fully promoted. In addition, the membrane material must also have certain corrosion resistance, chemical stability and mechanical strength. Summary of the invention

[0007] The purpose of the present invention is to provide a method for in-situ hydrogen production from seawater, using an IPN membrane as a phase change mass transfer layer to ensure that the phase change mass transfer layer has both high hydrophobicity and good water vapor permeability, so as to further improve the efficiency of in-situ hydrogen production from seawater electrolysis; in addition, the IPN membrane preparation method is simple to operate, the required equipment is easily available, the cost is controllable, and the yield rate is high.

[0008] To achieve the above object, the technical solution adopted by the present invention is: The method for in-situ hydrogen production from seawater described in the present invention comprises a phase change mass transfer tank, which comprises a seawater zone, a phase change mass transfer layer and an electrolyte zone, wherein the phase change mass transfer layer is located between the seawater zone and the electrolyte zone, and seawater is discharged from the seawater tank, passes through a pre-filter, a primary heat exchanger and a secondary heat exchanger in sequence, and enters the seawater zone of the phase change mass transfer tank for phase change mass transfer; the electrolyte enters the electrolyte zone of the phase change mass transfer tank from an electrolyte mixing tank; phase change mass transfer is carried out at the phase change mass transfer layer, and an IPN membrane is selected for the phase change mass transfer layer; the discharge from the electrolyte zone enters the electrolyzer for in-situ hydrogen production from seawater.

[0009] in: The preparation process of the IPN membrane includes the following steps: preparing cross-linked polyvinyl alcohol; adding diisocyanate, tetracarboxylic dianhydride and water into a polar solvent for prepolymerization reaction, then adding a fluorinating agent for modification to obtain a hydrophobic polyamic acid precursor; mixing the hydrophobic polyamic acid precursor, cross-linked polyvinyl alcohol and a polar solvent for swelling, then adding a dehydration catalyst and a cross-linking agent B for dehydration cyclization reaction, and performing a film-forming treatment to obtain an IPN membrane.

[0010] The preparation of the cross-linked polyvinyl alcohol comprises the following steps: dissolving polyvinyl alcohol in water to obtain a polyvinyl alcohol aqueous solution; and adding an initiator and a cross-linking agent A for cross-linking to obtain a cross-linked polyvinyl alcohol. The concentration of the polyvinyl alcohol aqueous solution is 15-30wt%.

[0011] The cross-linking temperature is 55-65° C., the cross-linking time is 20-35 min, the initiator is dibenzoyl peroxide; the cross-linking agent A is 1,3-dimethylurea; the mass ratio of the added initiator, cross-linking agent A, and polyvinyl alcohol is (0.03-0.06): (0.1-0.15):1.

[0012] The diisocyanate is one of toluene diisocyanate, diphenylmethane diisocyanate or hexamethylene diisocyanate; the tetracarboxylic dianhydride is pyromellitic dianhydride or 3,3',4,4'-benzophenonetetracarboxylic dianhydride; the polar solvent is one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide or N-methylpyrrolidone; the molar ratio of diisocyanate, tetracarboxylic dianhydride and water is 1:(1.1-1.2):(2.2-2.5).

[0013] The prepolymerization reaction temperature is 28-40°C, and the prepolymerization reaction time is 90-150min; the fluorinating agent is one of perfluorooctyl triethoxysilane, perfluoropropyl vinyl ether or 1H,1H,2H,2H-perfluorooctanol acrylate, the modification temperature is 50-65°C, and the modification time is 12-20min; the molar ratio of the fluorinating agent to the diisocyanate is (0.3-0.5):1.

[0014] The swelling time is 25-35 minutes; the dehydration catalyst is one of triethylamine, N-methyldiethanolamine, triethanolamine or lutidine, and the crosslinking agent B is trimesoyl chloride or aminopropyltriethoxysilane; the dehydration cyclization reaction temperature is 140-200°C, and the dehydration cyclization reaction time is 60-150 minutes; the molar ratio of the crosslinking agent B, the dehydration catalyst and the diisocyanate is (0.08-0.12): (0.02-0.06): 1; the mass ratio of polyvinyl alcohol and diisocyanate is (0.55-0.85): 1.

[0015] The film forming process includes two steps of pre-coating and spin coating. Both steps use a spin coater. During pre-coating, the rotation speed of the spin coater is set to 180-400 rad / min, and the pre-coating time is 18-25 minutes; during spin coating, the rotation speed of the spin coater is set to 1800-2800 rad / min, and the spin coating time is 10-20 minutes; the thickness of the obtained IPN is 0.5-1.2 μm. The purpose of pre-coating and spin coating is to form an IPN film layer with basic uniformity and adhesion on the surface of the substrate through pre-coating, which is beneficial to the spin coating efficiency during subsequent spin coating and the thickness uniformity and thickness control accuracy of the IPN film layer.

[0016] The temperature of the electrolyte in the electrolyte zone is 60-75°C; the electrolyte is a 25-35wt% potassium hydroxide solution; at the phase change mass transfer tank, the temperature of the seawater is higher than the temperature of the electrolyte, and the temperature difference is 8-15°C.

[0017] The pre-filter is provided with a ceramic ultrafiltration membrane; the material of the ceramic ultrafiltration membrane is one of aluminum oxide, zirconium oxide, titanium oxide or silicon oxide.

[0018] The beneficial effects of the present invention are as follows: (1) Since each unit of polyvinyl alcohol contains a hydroxyl group, these hydroxyl groups are densely arranged on one side of the polyvinyl alcohol molecular chain, which easily forms a hydrogen bond network, causing the molecular chains to be entangled and resulting in a decrease in the freedom of the molecular chains. This makes it difficult for the hydrophobic polyamic acid precursor to penetrate into the gaps between the polyvinyl alcohol molecular chains, which is not conducive to the formation of the IPN film. Therefore, by adding a cross-linking agent with higher molecular rigidity, such as 1,3-dimethyl urea, a cross-linked polyvinyl alcohol is prepared. The imino group in 1,3-dimethyl urea can be activated to react with hydroxyl groups. On the one hand, the hydroxyl density is reduced, and on the other hand, the cross-linking agent molecules can act as bridges to connect the originally independent polyvinyl alcohol molecular chains to form a more stable and regular cross-linked network system. This reduces the entanglement of the polyvinyl alcohol molecular chains and enables the hydrophobic polyamic acid precursor to be evenly distributed around the polyvinyl alcohol molecular chains.

[0019] (2) The fluorinating agent is not only a hydrophobic modifier of polyamic acid. Since the dehydration cyclization reaction of the hydrophobic polyamic acid precursor is an imidization reaction, it needs to react at a higher temperature. However, in a high temperature environment, polyamic acid sometimes undergoes thermal dissociation, triggering a free radical chain reaction, causing polyamic acid degradation. The fluorine atoms in the fluorinating agent can combine with free radicals to form more stable fluorinated free radicals. These fluorinated free radicals are not easy to trigger chain reactions, thereby helping to improve the thermal stability of the material.

[0020] (3) The present invention uses the principle of sequential generation. The polyvinyl alcohol molecular chain contains a large number of hydroxyl groups, which can form hydrogen bonds with water molecules to make the polyvinyl alcohol have good hydrophilicity. The hydrophobic polyamic acid precursor modified by hydrophobicity is infiltrated into the molecular gap of the hydrophilic polyvinyl alcohol network, and then under the action of a dehydration catalyst, multiple hydrophobic polyamic acid molecules are activated at high temperature. The amide group (-CONH2) at one end of one molecule and the carboxyl group in another molecule are dehydrated to form an imide bond (-CO-NH-CO-), and then cyclized on both sides of the polyvinyl alcohol molecular chain to generate a hydrophobic polyimide.

[0021] Since the hydrophobic polyimide surrounds the hydrophilic polyvinyl alcohol molecular chain, the seawater cannot spread on the hydrophobic surface and a micron-sized gap is formed between the seawater and the hydrophobic surface, thereby preventing impurities such as chloride ions in the seawater from entering the electrolyte through the hydrophobic surface. However, water vapor molecules can pass through this micron-sized gap and directly contact the hydroxyl groups in the cross-linked polyvinyl alcohol to form hydrogen bonds, thereby passing through the hydrophobic surface. Originally, it was difficult for a single substance to have both hydrophilicity and hydrophobicity at the same time, and it was difficult to adjust the balance of hydrophilicity / hydrophobicity. However, the present invention uses a polymer interpenetrating network (IPN) to compound the hydrophilic polyvinyl alcohol and the hydrophobic fluorinated modified polyimide into a uniform material through forced compatibility, and through repeated experiments, the balance of hydrophilicity / hydrophobicity is adjusted by adjusting the ratio of the reaction raw materials, so that the prepared IPN membrane can simultaneously exhibit hydrophilicity and hydrophobicity. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the flow chart of in-situ hydrogen production from seawater; Figure 2 It is a structural schematic diagram of the phase change mass transfer tank; Figure 3 is a scanning electron microscope image of the IPN film in Example 1; In the figure: 1. Seawater area; 2. Phase change mass transfer layer; 3. Electrolyte area. DETAILED DESCRIPTION

[0023] The present invention is specifically described and illustrated below in conjunction with embodiments.

[0024] Example 1 Preparation of IPN membrane: Add 120 g of polyvinyl alcohol and 500 g of deionized water into a three-necked flask, place the three-necked flask in a constant temperature water bath, set the water bath temperature to 85°C, start stirring until it is completely dissolved to obtain a polyvinyl alcohol aqueous solution; add 6 g of dibenzoyl peroxide and 18 g of 1,3-dimethylurea, set the water bath temperature to 60°C, stir for 25 minutes, centrifuge, and dry under reduced pressure to obtain cross-linked polyvinyl alcohol.

[0025] Prepare another clean and dry three-necked flask, add 148.03g of toluene diisocyanate, 203.95g of pyromellitic anhydride, 370g of deionized water and 900g of dimethyl sulfoxide into the three-necked flask, place the three-necked flask in a constant temperature water bath, set the water bath heating temperature to 35°C, start stirring, stir for 120min, then continue to add 113.07g of perfluoropropyl vinyl ether for modification, set the water bath heating temperature to 58°C, and modify for 15min; then pass into a centrifuge, centrifuge to remove impurities, and obtain a hydrophobic polyamic acid precursor.

[0026] Pour the hydrophobic polyamic acid precursor into a round-bottom flask, add 1000 g of dimethyl sulfoxide and cross-linked polyvinyl alcohol at room temperature, shake well, and swell for 28 minutes, then add 4.05 g of N-methyldiethanolamine and 20.31 g of trimesoyl chloride, mix well, and pass into a high-temperature reactor, set the heating temperature to 220°C, heat, and stir for 120 minutes to obtain a membrane solution.

[0027] The membrane solution was added to the substrate of the spin coater for film formation, the speed was set to 400 rad / min, and pre-coated at 80°C for 18 minutes; the polyvinyl alcohol aqueous solution was added to the substrate of the spin coater, the speed was set to 2800 rad / min, and high-speed spin coating was performed at 80°C for 10 minutes. After drying, rinsing, and re-drying, an IPN film was obtained. The film thickness was measured to be 1.2 μm, and the surface structure was as follows Figure 3 shown.

[0028] The tensile strength and elongation at break of the IPN film are tested according to GB / T 1040-2006, and the tensile strength is required to be ≥125MPa and the elongation at break is required to be ≥70%. Based on the differential principle, a laser displacement sensor is used to measure the thickness and thickness uniformity of the IPN film, and the thickness deviation of the film material per square meter is required to be within ±0.01μm. The liquid contact angle on the surface of the IPN film is measured by microscope photography combined with the bubble capture method, and the contact angle is required to be between 118-130°. After calculation, the yield rate is 94.1%.

[0029] Example 2 Preparation of IPN membrane: Add 120 g of polyvinyl alcohol and 500 g of deionized water into a three-necked flask, place the three-necked flask in a constant temperature water bath, set the water bath temperature to 85°C, start stirring until it is completely dissolved to obtain a polyvinyl alcohol aqueous solution; add 7.2 g of dibenzoyl peroxide and 16 g of 1,3-dimethylurea, set the water bath temperature to 55°C, stir for 35 minutes, centrifuge, and dry under reduced pressure to obtain cross-linked polyvinyl alcohol.

[0030] Prepare another clean and dry three-necked flask, add 212.72g of diphenylmethane diisocyanate, 314.98g of 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride, 468g of deionized water and 1500g of N-methylpyrrolidone into the three-necked flask, place the three-necked flask in a constant temperature water bath, set the water bath heating temperature to 40°C, start stirring, stir for 90 minutes, then continue to add 130.14g of perfluorooctyl triethoxysilane for modification, set the water bath heating temperature to 65°C, and modify for 12 minutes; then pass into a centrifuge, centrifuge to remove impurities, and obtain a hydrophobic polyamic acid precursor.

[0031] Pour the hydrophobic polyamic acid precursor into a round-bottom flask, add 1000 g of dimethyl sulfoxide and cross-linked polyvinyl alcohol at room temperature, shake well, and swell for 25 minutes, then add 5.16 g of triethylamine and 15.05 g of aminopropyltriethoxysilane, mix well, and pass into a high-temperature reactor, set the heating temperature to 180°C, heat, and stir for 150 minutes to obtain a membrane solution.

[0032] The membrane solution was added to the substrate of the spin coater for film formation, the rotation speed was set to 300 rad / min, and pre-coating was performed at 80°C for 21 minutes; the polyvinyl alcohol aqueous solution was added to the substrate of the spin coater, the rotation speed was set to 2300 rad / min, and high-speed spin coating was performed at 80°C for 16 minutes. After drying, rinsing, and re-drying, an IPN film was obtained. The film thickness was measured to be 0.9 μm.

[0033] The tensile strength and elongation at break of the IPN film are tested according to GB / T 1040-2006, and the tensile strength is required to be ≥125MPa and the elongation at break is required to be ≥70%. Based on the differential principle, a laser displacement sensor is used to measure the thickness and thickness uniformity of the IPN film, and the thickness deviation of the film material per square meter is required to be within ±0.01μm. The liquid contact angle on the surface of the IPN film is measured by microscope photography combined with the bubble capture method, and the contact angle is required to be between 118-130°. After calculation, the yield rate is 92.2%.

[0034] Example 3 Preparation of IPN membrane: Add 120 g of polyvinyl alcohol and 500 g of deionized water into a three-necked flask, place the three-necked flask in a constant temperature water bath, set the water bath temperature to 85°C, start stirring until it is completely dissolved to obtain a polyvinyl alcohol aqueous solution; add 3.6 g of dibenzoyl peroxide and 12 g of 1,3-dimethylurea, set the water bath temperature to 65°C, stir for 20 minutes, centrifuge, and dry under reduced pressure to obtain cross-linked polyvinyl alcohol.

[0035] Prepare another clean and dry three-necked flask, add 142.97g of hexamethylene diisocyanate, 222.48g of pyromellitic anhydride, 330g of deionized water and 1000g of N,N-dimethylformamide into the three-necked flask, place the three-necked flask in a constant temperature water bath, set the water bath heating temperature to 28°C, start stirring, stir for 150min, then continue to add 1H,1H,2H,2H-perfluorooctanol acrylate 142.17g for modification, set the water bath heating temperature to 50°C, and modify for 20min; then pass into a centrifuge, centrifuge to remove impurities, and obtain a hydrophobic polyamic acid precursor.

[0036] Pour the hydrophobic polyamic acid precursor into a round-bottom flask, add 1000 g of dimethyl sulfoxide and cross-linked polyvinyl alcohol at room temperature, shake well, and swell for 35 minutes, then add 2.54 g of triethanolamine and 22.58 g of aminopropyltriethoxysilane, mix well, and pass into a high-temperature reactor, set the heating temperature to 250°C, heat, and stir for 60 minutes to obtain a membrane solution.

[0037] The membrane solution was added to the substrate of the spin coater for film formation, the rotation speed was set to 180 rad / min, and pre-coated at 80°C for 25 minutes; the polyvinyl alcohol aqueous solution was added to the substrate of the spin coater, the rotation speed was set to 1800 rad / min, and high-speed spin coating was performed at 80°C for 20 minutes. After drying, rinsing, and re-drying, an IPN film was obtained. The film thickness was measured to be 0.5 μm.

[0038] The tensile strength and elongation at break of the IPN film are tested according to GB / T 1040-2006, and the tensile strength is required to be ≥125MPa and the elongation at break is required to be ≥70%. Based on the differential principle, a laser displacement sensor is used to measure the thickness and thickness uniformity of the IPN film, and the thickness deviation of the film material per square meter is required to be within ±0.01μm. The liquid contact angle on the surface of the IPN film is measured by microscope photography combined with the bubble capture method, and the contact angle is required to be between 118-130°. After calculation, the yield rate is 91.5%.

[0039] Example 4 In-situ electrolysis of seawater to produce hydrogen: according to Figure 1 and Figure 2 As shown, a seawater in-situ hydrogen production device is constructed; seawater is discharged from a seawater tank, passes through a pre-filter, a primary heat exchanger, and a secondary heat exchanger in sequence, and enters the seawater zone 1 of a phase change mass transfer tank for phase change mass transfer; the electrolyte enters the electrolyte zone 3 of the phase change mass transfer tank from an electrolyte mixing tank; phase change mass transfer is carried out at the phase change mass transfer layer 2; the discharge from the electrolyte zone 3 enters the electrolyzer for seawater in-situ hydrogen production.

[0040] A ceramic ultrafiltration membrane is installed in the pre-filter; the material of the ceramic ultrafiltration membrane is one of aluminum oxide, zirconium oxide, titanium oxide or silicon oxide.

[0041] The phase change mass transfer tank consists of a seawater zone 1, an electrolyte zone 3 and a phase change mass transfer layer 2, and the phase change mass transfer layer 2 is located between the seawater zone 1 and the electrolyte zone 3; 1500mL of a 35wt% potassium hydroxide aqueous solution is passed into the electrolyte zone 3, and the temperature of the potassium hydroxide aqueous solution is 60°C; 1500mL of pre-filtered seawater is passed into the seawater zone 1, and the seawater temperature is 70°C; the phase change mass transfer layer 2 is the IPN membrane prepared in Example 1.

[0042] The electrolytic cell is powered at 230 mA / cm 2 The electrolysis was carried out under the same conditions for 60 minutes, and the hydrogen obtained at the cathode was collected and measured at room temperature. The measurement showed that the hydrogen production efficiency was 432.3 L / h.

[0043] Example 5 In-situ electrolysis of seawater to produce hydrogen: according to Figure 1 and Figure 2 As shown, a seawater in-situ hydrogen production device is constructed; seawater is discharged from a seawater tank, passes through a pre-filter, a primary heat exchanger, and a secondary heat exchanger in sequence, and enters the seawater zone 1 of a phase change mass transfer tank for phase change mass transfer; the electrolyte enters the electrolyte zone 3 of the phase change mass transfer tank from an electrolyte mixing tank; phase change mass transfer is carried out at the phase change mass transfer layer 2; the discharge from the electrolyte zone 3 enters the electrolyzer for seawater in-situ hydrogen production.

[0044] A ceramic ultrafiltration membrane is installed in the pre-filter; the material of the ceramic ultrafiltration membrane is one of aluminum oxide, zirconium oxide, titanium oxide or silicon oxide.

[0045] The phase change mass transfer tank consists of a seawater zone 1, an electrolyte zone 3 and a phase change mass transfer layer 2, and the phase change mass transfer layer 2 is located between the seawater zone 1 and the electrolyte zone 3; 1500mL of a 30wt% potassium hydroxide aqueous solution is passed into the electrolyte zone 3, and the temperature of the potassium hydroxide aqueous solution is 67°C; 1500mL of pre-filtered seawater is passed into the seawater zone 1, and the seawater temperature is 75°C; the phase change mass transfer layer 2 is the IPN membrane prepared in Example 2.

[0046] The electrolytic cell is powered at 230 mA / cm 2 The electrolysis was carried out under the same conditions for 60 minutes, and the hydrogen obtained at the cathode was collected and measured at room temperature. The measurement showed that the hydrogen production efficiency was 425.6L / h.

[0047] Example 6 In-situ electrolysis of seawater to produce hydrogen: according to Figure 1 and Figure 2As shown, a seawater in-situ hydrogen production device is constructed; seawater is discharged from a seawater tank, passes through a pre-filter, a primary heat exchanger, and a secondary heat exchanger in sequence, and enters the seawater zone 1 of a phase change mass transfer tank for phase change mass transfer; the electrolyte enters the electrolyte zone 3 of the phase change mass transfer tank from an electrolyte mixing tank; phase change mass transfer is carried out at the phase change mass transfer layer 2; the discharge from the electrolyte zone 3 enters the electrolyzer for seawater in-situ hydrogen production.

[0048] A ceramic ultrafiltration membrane is installed in the pre-filter; the material of the ceramic ultrafiltration membrane is one of aluminum oxide, zirconium oxide, titanium oxide or silicon oxide.

[0049] The phase change mass transfer tank consists of a seawater zone 1, an electrolyte zone 3 and a phase change mass transfer layer 2, and the phase change mass transfer layer 2 is located between the seawater zone 1 and the electrolyte zone 3; 1500mL of a 25wt% potassium hydroxide aqueous solution is introduced into the electrolyte zone 3, and the temperature of the potassium hydroxide aqueous solution is 60°C; 1500mL of pre-filtered seawater is introduced into the seawater zone 1, and the seawater temperature is 75°C; the phase change mass transfer layer 2 is the IPN membrane prepared in Example 3.

[0050] The electrolytic cell is powered at 230 mA / cm 2 The electrolysis was carried out under the same conditions for 60 minutes, and the hydrogen obtained at the cathode was collected and measured at room temperature. The measurement showed that the hydrogen production efficiency was 426.9 L / h.

[0051] Comparative Example 1 The IPN membrane in Example 4 was replaced by a PTFE membrane, and the remaining steps were the same as those in Example 4. After measurement, the production efficiency of hydrogen was 330.1 L / h.

[0052] Comparative Example 2 A cross-linked polyvinyl alcohol was prepared and directly subjected to film-forming treatment without using a hydrophobic polyamic acid precursor, and the remaining steps were the same as in Example 1 to obtain a polyvinyl alcohol film. Hydrogen was produced according to the method described in Example 4, except that the phase change mass transfer layer 2 was replaced by the polyvinyl alcohol film obtained in Comparative Example 2. After measurement, the hydrogen production efficiency was 240.5 L / h.

[0053] Comparative Example 3 Only a hydrophobic polyamic acid precursor is used for film formation, the hydrophobic polyamic acid precursor and the polar solvent are mixed and swollen, and then a dehydration catalyst and a crosslinking agent B are added to carry out a dehydration cyclization reaction, and a membrane material is obtained after a film forming treatment. The remaining steps are the same as in Example 1. Hydrogen is produced according to the method described in Example 4, except that the phase change mass transfer layer 2 is replaced by the hydrophobic polyimide membrane obtained in Comparative Example 3. After measurement, the production efficiency of hydrogen is 138.2L / h.

[0054] Comparative Example 4 The crosslinking agent A is replaced by a silane coupling agent, γ-(methacryloyloxy)propyltrimethoxysilane, and the remaining steps are the same as in Example 1. Hydrogen is produced according to the method described in Example 4, except that the phase change mass transfer layer 2 is replaced by the IPN membrane prepared in Comparative Example 4. After measurement, the hydrogen production efficiency is 315.5 L / h.

[0055] Comparative Example 5 The fluorinating agent was replaced by a silane coupling agent, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, and the remaining steps were the same as in Example 1. Hydrogen was produced according to the method described in Example 4, except that the phase change mass transfer layer 2 was replaced by the IPN membrane prepared in Comparative Example 5. After measurement, the hydrogen production efficiency was 311.7 L / h.

[0056] Although the present invention is described in detail by way of embodiments, the present invention is not limited thereto. Without departing from the spirit and substance of the present invention, those skilled in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions should all be within the scope of the present invention.

Claims

1. A method for in-situ hydrogen production from seawater, comprising a phase change mass transfer tank, the phase change mass transfer tank comprising a seawater region (1), a phase change mass transfer layer (2) and an electrolyte region (3), the phase change mass transfer layer (2) being located between the seawater region (1) and the electrolyte region (3), characterized in that: Seawater is discharged from a seawater tank and passes through a pre-filter, a primary heat exchanger, and a secondary heat exchanger in sequence, and enters the seawater area (1) of a phase change mass transfer tank for phase change mass transfer; the electrolyte enters the electrolyte area (3) of the phase change mass transfer tank from an electrolyte mixing tank; the phase change mass transfer is carried out at the phase change mass transfer layer (2), and an IPN membrane is selected for the phase change mass transfer layer (2); the discharge from the electrolyte area (3) enters the electrolytic cell for in-situ hydrogen production from seawater.

2. The method for in-situ hydrogen production from seawater according to claim 1, characterized in that: The IPN membrane preparation process includes the following steps: preparing cross-linked polyvinyl alcohol; adding diisocyanate, tetracarboxylic dianhydride and water into a polar solvent for prepolymerization reaction, then adding a fluorinating agent for modification to obtain a hydrophobic polyamic acid precursor; mixing the hydrophobic polyamic acid precursor, cross-linked polyvinyl alcohol and a polar solvent for swelling, then adding a dehydration catalyst and a cross-linking agent B for a dehydration cyclization reaction, and obtaining an IPN membrane through a film-forming treatment.

3. The method for in-situ hydrogen production from seawater according to claim 2, characterized in that: The preparation of cross-linked polyvinyl alcohol includes the following steps: The polyvinyl alcohol is dissolved in water to obtain a polyvinyl alcohol aqueous solution; and an initiator and a crosslinking agent A are added to perform crosslinking to obtain a crosslinked polyvinyl alcohol.

4. The method for in-situ hydrogen production from seawater according to claim 3, characterized in that: The cross-linking temperature is 55-65°C, the cross-linking time is 20-35min, the initiator is dibenzoyl peroxide; the cross-linking agent A is 1,3-dimethylurea; the mass ratio of the added initiator, cross-linking agent A, and polyvinyl alcohol is (0.03-0.06): (0.1-0.15):

1.

5. The method for in-situ hydrogen production from seawater according to claim 2, characterized in that: The diisocyanate is one of toluene diisocyanate, diphenylmethane diisocyanate or hexamethylene diisocyanate; the tetracarboxylic dianhydride is pyromellitic dianhydride or 3,3',4,4'-benzophenonetetracarboxylic dianhydride; the polar solvent is one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide or N-methylpyrrolidone; the molar ratio of diisocyanate, tetracarboxylic dianhydride and water is 1:(1.1-1.2):(2.2-2.5).

6. The method for in-situ hydrogen production from seawater according to claim 2, characterized in that: The prepolymerization reaction temperature is 28-40°C, and the prepolymerization reaction time is 90-150min; the fluorinating agent is one of perfluorooctyl triethoxysilane, perfluoropropyl vinyl ether or 1H,1H,2H,2H-perfluorooctanol acrylate, the modification temperature is 50-65°C, and the modification time is 12-20min; the molar ratio of the fluorinating agent to the diisocyanate is (0.3-0.5):

1.

7. The method for in-situ hydrogen production from seawater according to claim 2, characterized in that: The swelling time is 25-35 minutes; the dehydration catalyst is one of triethylamine, N-methyldiethanolamine, triethanolamine or lutidine, and the crosslinking agent B is trimesoyl chloride or aminopropyltriethoxysilane; the dehydration cyclization reaction temperature is 180-250°C, and the dehydration cyclization reaction time is 60-150 minutes; the molar ratio of the crosslinking agent B, the dehydration catalyst and the diisocyanate is (0.08-0.12): (0.02-0.06): 1; the mass ratio of polyvinyl alcohol and diisocyanate is (0.55-0.85):

1.

8. The method for in-situ hydrogen production from seawater according to claim 2, characterized in that: The film forming process includes two steps: pre-coating and spin coating. A spin coater is used in both steps. When pre-coating, the speed of the spin coater is set to 180-400 rad / min and the pre-coating time is 18-25 min. When spin coating, the speed of the spin coater is set to 1800-2800 rad / min and the spin coating time is 10-20 min.

9. The method for in-situ hydrogen production from seawater according to claim 1, characterized in that: The temperature of the electrolyte in the electrolyte zone (3) is 60-75°C; the electrolyte is a 25-35wt% potassium hydroxide solution; at the phase change mass transfer tank, the temperature of the seawater is higher than the temperature of the electrolyte, and the temperature difference is 8-15°C.

10. The method for in-situ hydrogen production from seawater according to claim 1, characterized in that: A ceramic ultrafiltration membrane is installed in the pre-filter; the material of the ceramic ultrafiltration membrane is one of aluminum oxide, zirconium oxide, titanium oxide or silicon oxide.

Citation Information

Patent Citations

  • Seawater in-situ self-trapping hydrogen production device, system and method based on polyelectrolyte gel

    CN113088986A

  • Non-pure water solution electrolytic hydrogen production device, system and method based on liquid phase moisture absorption

    CN114481164A

  • Polymer microporous membrane and preparation method thereof, and water treatment equipment

    CN111450707A

  • Porous composite membrane for hydrogen production by alkaline electrolyzed water and preparation method of porous composite membrane

    CN117604571A

  • Energy-consumption-free water replenishing device for seawater desalination-free in-situ direct hydrogen production

    CN117684216A

Cited By

  • Method for preparing polyimide gas separation membrane through in-situ fluorination

    CN121490605A